Anti-Cancer Activity of Maize Bioactive Peptides - Díaz-Gómez, Jorge L.; Castorena-Torres, Fabiola; Preciado-Ortiz, Ricardo E.; García-Lara, Silverio (Frontiers in Chemistry, 2017)
Cancer is one of the main chronic degenerative diseases worldwide. In recent years, consumption of whole-grain cereals and their derivative food products has been associated with a reduced risk of various types of cancer. The main biomolecules in cereals include proteins, peptides, and amino acids, all of which are present in different quantities within the grain. Some of these peptides possess nutraceutical properties and exert biological effects that promote health and prevent cancer. In this review, we report the current status and advances in knowledge regarding the bioactive properties of maize peptides, such as antioxidant, antihypertensive, hepatoprotective, and anti-tumor activities. We also highlight the potential biological mechanisms through which maize bioactive peptides exert anti-cancer activity. Finally, we analyze and emphasize the potential applications of maize peptides.